2021
DOI: 10.3390/polym13050710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Top Electrodes on the Nonvolatile Resistive Switching Properties of Citrus Thin Films

Abstract: Natural citrus thin films on an indium tin oxide (ITO)/glass substrate were synthesized using the solution method for resistive random access memory (RRAM) applications. The results indicated that the citrus memory device possessed stable resistive switching behavior. For a clear understanding of the role of the interface reaction between the top metal electrode and the citrus film, we investigated the influences of various top electrode (TE) materials on the resistive switching in TE/citrus/ITO devices. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The threestage current variation of the device is consistent with the space charge limited conduction (SCLC) model [14,15], further corroborating the underlying current conduction mechanism related to the formation of localized filament paths. To further explore the conduction mechanism of ACG01 device, we have analyzed the trend of the LRS current with temperature at a voltage of 0.1 V. As shown in figure 11(b), the relationship between the resistance of the LRS and temperature in the range of 300-340 K is depicted, measured by applying a voltage of 0.1 V. It is observed that the resistance decreases with increasing temperature, attributed to typical semiconductor behavior [16,17]. Furthermore, during the operation of the resistive switch, in the LRS, the dehydrogenation reaction assists in the formation of conjugated double bonds in the carbon layer, yielding the conductive sp 2 carbon filaments [18].…”
Section: Resultsmentioning
confidence: 99%
“…The threestage current variation of the device is consistent with the space charge limited conduction (SCLC) model [14,15], further corroborating the underlying current conduction mechanism related to the formation of localized filament paths. To further explore the conduction mechanism of ACG01 device, we have analyzed the trend of the LRS current with temperature at a voltage of 0.1 V. As shown in figure 11(b), the relationship between the resistance of the LRS and temperature in the range of 300-340 K is depicted, measured by applying a voltage of 0.1 V. It is observed that the resistance decreases with increasing temperature, attributed to typical semiconductor behavior [16,17]. Furthermore, during the operation of the resistive switch, in the LRS, the dehydrogenation reaction assists in the formation of conjugated double bonds in the carbon layer, yielding the conductive sp 2 carbon filaments [18].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the HRS to LRS ratio for Al/CZTS/ITO device is maximum (~32.20) in comparison to other top electrodes, e. g., Cu (>4) and Ag (~2). The large ratio with Al as top electrode is attributed to the digital switching, giving rise to the large current difference in LRS to HRS, as a consequence of lower work function of Al, as the resistive switching ratio gets better with decreasing the work function of the top electrode [38,39] . Further endurance characterization is measured up to 100 cycles at V write =0.3 V and V erase =−0.3 V, for Cu and Ag top electrode and V write =−0.3 V and V erase =0.3 V for Al top electrode, with 30 msec switching speed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that top electrode plays the vital role in the resistive switching. Lin et al, [38] showed the increase in the I on /I off ratio ~10 3 with changing the top electrode Al from Au and Ti and attributed it to the better dissolution property of Al as compared to Au and Ti. Similar observations are reported by Muñoz-Gorriz et al, [56] for Cu as top electrode with respect to Ni.…”
Section: Impedance Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…the Al 2 O 3 thin film of Interface control of the filament types and the resistive switching behavior of apple pectin RRAM devices were systematically investigated using different sputtering plasmas. 10 Chang et al A AgG thin film produced by the solution method of metal salts dissolved in gelatin is presented. Its simple fabrication method ensures the uniform distribution of Ag dots.…”
mentioning
confidence: 99%